EVALUASI KESIAPAN GURU DALAM MENERAPKAN INOVASI PEMBELAJARAN BERBASIS TPACK (TECHNOLOGICALPEDAGOGICAL CONTENT KNOWLEDGE) PADA PEMBELAJARAN ABAD 21 DI KOTA SEMARANG - Susanti, Martien Herna; Setiajid; Anandha (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This article aims to evaluate teachers' readiness to implement TPACK-based learning innovations in 21st-century learning. 21st-century learning is characterized by curriculum changes from teacher-centered to student-centered learning approaches. It is intended that students have thinking and learning skills. The research method used a qualitative approach. The results showed that the majority of teachers in Semarang City, according to age, are part of the millennial generation. This is very supportive of the demands of teachers in the 21st century related to technological literacy skills and the use of ICT as a learning resource. At this time, the role of teachers is more as facilitators, motivators, and inspirers for students in finding and utilizing learning resources. Consequently, all teachers must have adequate knowledge, skills, and technological competencies that are included in learning. The research concludes that 21st-century learning changes the mindset of the educational process that previously took place conventionally shifting to learning based on the utilization of communication and information technology. The lack of equitable skills currently owned makes the need for teacher evaluation readiness in implementing TPACK-based learning innovations so that learning activities are in accordance with the development of information and communication technology in 21st-century learning.